A new genus and species from southwestern China in the Frankliniella genus-group (Thysanoptera: Thripidae) - Zhang, Hongrui; Mound, Laurence A.; Xie, Yonghui (Zootaxa, 2010)
A new genus and species, Yaobinthrips yangtzei, are described from Southwestern China sharing many character states with the Austro-Oriental genus Parabaliothrips within the Frankliniella genus-group. Within this group the new species is distinguished by the presence of tergal craspeda, a pair of uniquely bulbous modified setae on the fore tibiae, enlarged fore femora with a basal tooth, and paired small pore plates on sternum VI of females.